A Mean‐Variance Benchmark for Intertemporal Portfolio Theory. (February 2014) - COCHRANE, JOHN H.
ABSTRACT Mean‐variance portfolio theory can apply to streams of payoffs such as dividends following an initial investment. This description is useful when returns are not independent over time and investors have nonmarketed income. Investors hedge their outside income streams. Then, their optimal payoff is split between an indexed perpetuity—the risk‐free payoff—and a long‐run mean‐variance efficient payoff. "Long‐run" moments sum over time as well as states of nature. In equilibrium, long‐run expected returns vary with long‐run market betas and outside‐income betas. State‐variable hedges do not appear.